4CPS-056 Proper use of antifungals: implementation of operational multidisciplinary teams dedicated to antifungals. (24th March 2020) - Audureau, P; Meyer, F; Charmillon, A; Henard, S; Demore, B
Abstract : Background and importance: There is an urgent need to establish the proper systemic use of antifungals because of drug resistance and a limited therapeutic arsenal. In June 2018, we created two operational multidisciplinary teams, each comprising a pharmacy resident and an infectious diseases specialist. With prescription assistant software and a data gathering document, residents analysed and validated prescriptions daily. They reappraised each case with the infectious diseases specialist once a week. Aim and objectives: To produce a summarised report of the analyses on antifungal prescriptions. This report allowed us to measure the performance of the newly created operational multidisciplinary teams. Material and methods: All antifungal prescriptions given to adults, oral and intravenous, were analysed in a prospective way from 18 June 2018 to 1 March 2019. The data gathered were patient identity, antifungal prescriptions (molecule, start date, posology and administration route), antifungal indication, patient biological check-up, and clinical and biological proofs. For each prescription, we evaluated the relevance of the indication and the overall compliance with the prescription. Results: A total of 653 prescriptions were analysed for this study, relating to 383 patients. On average, residents analysed 64 prescriptions a month and 59 were appraised by the operational multidisciplinary teams. Haematology was the most prescribing unit (49.8%). Caspofungin (35%), using the intravenous route, or posaconazole (35%), using the oral route, were the most prescribed antifungals. Indications were probabilistic 35% of the time, prophylactic 34% of the time and documented 30% of the time. Documented infections were mainly invasive candidiasis (57%) and pulmonary aspergillosis (32%). Among the 653 prescriptions, 96 were the subject of a pharmaceutical opinion, mainly for improper dosage (50%) or missing a loading dose (29.2%); 84% of prescriptions were re-evaluated by the infectious diseases specialist. Opinions were mainly about switching molecules (32%) and stopping therapy (28%). A total of 75.8% of prescriptions were successfully updated. Comparing our results with those obtained in 2015 in our hospital, the global conformity of the prescription (indication, molecule choice, posology, treatment length, lack of therapeutic alternatives) was up from 81.5% to 87%. Conclusion and relevance: Implementation of operational multidisciplinary teams helped reduce the number of issues and thus contributed to improvement in the quality of prescriptions. References and/or acknowledgements: No conflict of interest.